DIVERSITY OF WETLAND FISH AND ITS IMPACT ON THE INCOME OF FISHERMEN COMMUNITY OF ASSAM - DEKA, TAPAN KUMAR; KAKATI, M.; GOSWAMI, M. M. (Journal of Indian Fisheries Association, 2015)
A survey was conductd in 3,000 fishermen households surrounding 54 wetlands (Beels) of Assam. The fish diversity of the wetlands has been decreasing during the last few years due to some extrinsic and intrinsic factors. The total number of fish species recorded so far during the present study is 67 belonging to 21 families. Cyprinidae is the most dominant family represented by major group species (8), intermediate group species (3) and minor group species (12) of high commercial value. Among these three groups, the diversity of fish species is higher in the minor group fish. The present paper deals with the economic condition of the fishermen who mainly fish in the wetlands. The economic condition of the fishermen community is found very poor. The income of fishermen varies from Rs.4,4 78.00 to Rs. 7,484.00 per annum. A regression analysis shows that the income of fishermen is not dependent alone on the fish production but it is exclusively dependent on the value of the fish catch. All the three groups (in terms of value) have significant influence at 10.00% confidence level. But analysis of shows that the intermediate fish group exhibits the highest influence on the variation of the fishermen income followed by minor and major group respectively. Keywords :Fish diversity, Fishermen, Fishing income, Wetlands